Energy transfer and 2.0 μm emission in Tm3+/Ho3+ co-doped α-NaYF4 single crystals. (April 2016) - Feng, Zhigang; Yang, Shuo; Xia, Haiping; Wang, Cheng; Jiang, Dongsheng; Zhang, Jian; Gu, Xuemei; Zhang, Yuepin; Chen, Baojiu; Jiang, Haochuan
Graphical abstract: Highlights: Cubic NaYF4 single crystals co-doped with ∼1.90 mol% Tm 3+ and various Ho 3+ concentrations were grown by Bridgman method. The maximum fluorescence lifetime was 23.23 ms for Tm 3+ (1.90 mol%)/Ho 3+ (3.89 mol%) co-doped α-NaYF4 . The obtained energy transfer rate ( W ET ) and energy transfer efficiency ( η ) of Tm 3+ : 3 F4 are 1077 s −1 and 95.0%, respectively. The maximum emission cross section reached 1.06 × 10 −20  cm 2 . Abstract: Cubic NaYF4 single crystals co-doped with ∼1.90 mol% Tm 3+ and various Ho 3+ concentrations were grown by Bridgman method. The energy transfer from Tm 3+ to Ho 3+ and the optimum fluorescence emission around 2.04 μm of Ho 3+ ion were investigated based on the measured absorption spectra, emission spectra, emission cross section and decay curves under excitation of 800 nm LD. The emission intensity at 2.04 μm increased with the increase of Ho 3+ concentration from 0.96 mol% to 3.89 mol% when the concentration of Tm 3+ was held constantly at ∼1.90 mol%. Moreover, the maximum emission cross section reached 1.06 × 10 −20  cm 2 and the maximum fluorescence lifetime was 23.23 ms for Tm 3+ (1.90 mol%)/Ho 3+ (3.89 mol%) co-doped one. According to the measured lifetime of Tm 3+ single-doped and Tm 3+ /Ho 3+ co-doped samples, the maximum energy transfer efficiency of Tm 3+ : 3 F4 level was 95.0%. Analysis on the fluorescence dynamics indicated that electric dipole–dipole is dominant for the energy transfer from Tm 3+ to Ho 3+ .